Comparison of emotional intelligence, body image, and quality of life between rhinoplasty candidates and control group - Nikzad Shahidi; Farshad Mahdavi; Mehdi Khanbabayi Gol (Wolters Kluwer Medknow Publications, 2020)
INTRODUCTION: Psychological factors affect the tendency of individuals toward cosmetic surgeries although their contribution has not been clearly understood. Therefore, the current study aimed at comparing the emotional intelligence, body image, and quality of life between rhinoplasty candidates and the control group. METHODS: The current case-control study was conducted on 160 individuals referring to Rhinoplasty Clinic of Imam Reza Hospital in Tabriz, Iran, from 2018 to 2019. The tools used in this study including demographic information, Schering's emotional intelligence questionnaire (α = 0.75-0.85), the 36-item Short Form Health Survey Questionnaire (α = 0.75), and body image (α = 0.77-0.91) were used to collect data. Data were analyzed by the Kolmogorov-Smirnov and t-tests for the two independent groups. P < 0.05 was considered as the level of significance. RESULTS: There was no significant difference between the groups in terms of the overall mean of emotional intelligence and its subcomponents (P > 0.05), except social skills, such as self-awareness (P = 0.019). Appearance evaluation and appearance orientation variables were statistically significant between the two groups (P < 0.05), while the quality of life was not statistically significant (P = 0.051). CONCLUSION: In the psychological parameters studied, we found that the appearance evaluation and social skills of the rhinoplasty applicants are low, and it is better to have interventions before the rhinoplasty in people who have difficulty with these variables.